Reducing ammonia levels in catfish cultivation water using several aquatic plants - Mustaqim Mustaqim; Mutasar Mustasar; Yusrizal Akmal; Mida Wahyuni; T. Irfan Fajri; Zaitun Ritaqwin (Depik, 2022)
Catfish farming is one of the businesses that is very much in demand by the community, because it can improve the community's economy. However, not all catfish farming businesses can produce maximum results. This can be caused by several factors, both from feed, management and water quality. Decrease in water quality can be caused by feces and fish feed residue. Poor water quality can cause the growth process, physiology and level of fish behavior to be disturbed. Efforts that can be done is to use aquatic plants as phytoremediation. The plants used in this study were Azolla sp, Eichhornia crassipes, Lemna sp, Ipomoea aquatic. The design used in this study was a completely randomized design with 4 treatments and 3 replications. The parameters observed in this study were ammonia levels, pH, and plant population. The results showed that Eichhornia crassipes and Lemna sp were able to reduce ammonia levels in catfish cultured water by 0.01 mg/l at the end of the study.Keywords:AmmoniaWater plantsCatfish